New information on the etiology and biological targets of wounds associated with diabetes - Ghosh, Niladry S.; Dubey, Anubhav; Kumari, Mamta (Journal of Applied Pharmaceutical Research, 2025)
Background: Wound healing is a complex process that advances through inflammation, proliferation, and remodelling phases. Diabetes precipitates numerous ailments that obstruct practically all of these reparative processes. Methodology: We performed a literature search on ScienceDirect and PubMed databases using various keywords, including "Diabetes Wound Healing." The search was refined by applying relevant filters to obtain the most pertinent articles for this review article's objective. Results: Patients with diabetes may incur wounds during or after medical interventions. The wound healing process comprises remodelling, proliferation, and inflammation. Diabetes impedes nearly all of these healing processes through various pathological changes. This study primarily examines the molecular pathways of inflammatory substances, including growth stimulants and other factors that hinder wound healing. It also examines molecular targets and the current advancements in wound care and complete healing. Conclusion: Based on our investigation, we identified several practical approaches for treating wound inflammation and proposed that combining these strategies may yield the most significant results in our research domain.